The price of whole-genome sequencing may be decreasing, but who will be sequenced?. (May 2017) - Marshall, Deborah A; MacDonald, Karen V; Robinson, Jill Oliver; Barcellos, Lisa F; Gianfrancesco, Milena; Helm, Monica; McGuire, Amy; Green, Robert C; Douglas, Michael P; Goldman, Michael A; Phillips, Kathryn A
Aim: Since whole-genome sequencing (WGS) information can have positive and negative personal utility for individuals, we examined predictors of willingness to pay (WTP) for WGS.Patients & methods: We surveyed two independent populations: adult patients (n = 203) and college seniors (n = 980). Ordinal logistic regression models were used to characterize the relationship between predictors and WTP.Results: Sex, age, education, income, genomic knowledge and knowing someone who had genetic testing or having had genetic testing done personally were associated with significantly higher WTP for WGS. After controlling for income and education, males were willing to pay more for WGS than females.Conclusion: Differences in WTP may impact equity, coverage, affordability and access, and should be anticipated by public dialog about related health policy.